Russian Federation : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Russia entered 2014 with declining potential growth owing to the stabilization of oil prices, stalled structural reforms, weak investment, declining total factor productivity, and adverse population dynamics. In addition, the ongoing slowdown was exacerbated by the dual external shocks from the sharp decline in oil prices and sanctions. The authorities took measures to stabilize the economy and the financial system. Russia is expected to be in recession in 2015 owing to the sharp drop in oil prices and sanctions. Growth should resume in 2016 while inflation continues to decline.